Hubungan Pengetahuan Minuman Tradisional Moke dan Kontrol Sosial dengan Perilaku Konsumsi Alkohol Pemuda di Kota Kupang - Katharina Noviyani Lama Tokan; Djakariah Djakariah; Esry Defriana Tosi (Jayapangus Press, 2026)
This study examines the relationship between knowledge of traditional Moke beverage and social control with alcohol consumption behavior among youth in Kupang City, where Moke , a distilled palm sap beverage central to East Nusa Tenggara (NTT) culture has shifted from ritual contexts to unregulated recreational practice. A quantitative descriptive-correlational cross-sectional design was employed with 100 respondents aged 17 – 30 years selected through purposive sampling. Data were collected using a validated 35-item Likert scale questionnaire. Assumptions of normality, linearity, and homogeneity were confirmed prior to analysis. Moke knowledge showed a significant weak positive relationship with consumption behavior (r = 0.228; p = 0.023), indicating that cultural familiarity with Moke reinforces rather than restrains consumption. Social control demonstrated a significant moderate negative relationship (r = 0.536; p = 0.000), with the belief dimension scoring lowest, reflecting erosion of internalized normative values due to urbanization. Simultaneously, both variables explained 35.2% of the variance in consumption behavior (R = 0.593; F = 26.362; p = 0.000). Effective intervention must integrate normative value internalization with community-based social control reinforcement, particularly revitalizing customary institutions and family supervision.